2010
DOI: 10.4028/www.scientific.net/amr.126-128.773
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Milling Hardened SKD Steel Using Micro CBN Ball-End Mills

Abstract: Micro ball-end milling process features the ability of machining complex surfaces, precision machining accuracy, and excellent machined surface roughness. However, because the diameter of a micro milling tool is very small, a rapid progress of tool wear or even tool breakage usually happens when machining a high-strength hardened mold steel using improper machining parameters. As a result, the machining cost would rise due to the quality defect in machined workpiece. In this study, to investigate how the machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…Although Liu et al [1] had reported the machining characteristics in the micro ball end milling without the inclination of the spindle, it is hard to say that the cutting performances by the micro ball end mill are sufficiently investigated. In order to obtain a fine finished surface of mold with an inclined plane and a free form surface, it is necessary to understand the characteristics of the micro ball end milling so that the tool wear reduces and the machining accuracy improves.…”
Section: Introductionmentioning
confidence: 99%
“…Although Liu et al [1] had reported the machining characteristics in the micro ball end milling without the inclination of the spindle, it is hard to say that the cutting performances by the micro ball end mill are sufficiently investigated. In order to obtain a fine finished surface of mold with an inclined plane and a free form surface, it is necessary to understand the characteristics of the micro ball end milling so that the tool wear reduces and the machining accuracy improves.…”
Section: Introductionmentioning
confidence: 99%